Isolamento, identificação e caracterização de linhagem de levedura quanto ao crescimento e fermentação utilizando meios sintéticos com pentoses e hidrolisado de bagaço de cana-de-açúcar - Martini, Cristina [UNESP] (2014)
The search for new yeast species able to ferment pentoses is one of the challenges towards the difficulties involving the technology on the production of second generation ethanol. Besides, the usage of lignocelulosic residues demands a step of hydrolysis for the depolymerization of the hemicelulosic fraction. Acids have been used frequently due to the low cost and high efficiency. However, inhibitors may also be released along with the sugars, inhibiting the fermentative activity of the yeasts. In this context, this study aimed to isolate yeast strains from natural sources (sugar cane juice, bagasse and rhizosphere, and corn straw), the presumptive evaluation of the pentose fermentation ability and the identification of the selected strain, which was evaluated regarding the ability to grow and ferment pentose by using synthetic media under different environmental conditions as well as acid hydrolysates obtained from sugar cane bagasse. Among 350 isolates, 39 displayed fermentative activity of arabinose (56.4%) or xylose (38.5%) or both (5.1%). One of the yeast strains that showed both arabinose and xylose fermentation (number 311), isolated from sugar cane juice, was identified by the amplification of D1/D2 region of the 26S gene and ITS region from the ribosomal DNA as Meyerozyma guilliermondii. This strain was evaluated regarding the influence of the carbon source (glucose, xylose or arabinose), pH (3.5; 4.5; 5.5) and temperature (30 oC, 35 oC, 40 oC) upon the growth, and the influence of pH (4.5; 5.5) and temperature (30 oC, 35 oC) upon the fermentation of xylose in concentrations ranging from 40 g/L to 100 g/L in synthetic media. Varying initial pH values and temperatures of incubation did not result in differences in the specific growth rate of M. guilliermondii when growing in 20 g/L arabinose, xylose or glucose. In fermentation assays, the increase in the xylose concentration did not bring about a higher alcohol production. A...